PENGARUH FREE CASH FLOW, LEVERAGE, PROFITABILITAS, LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN - Andre Hand Prastya; Fitri Yani Jalil (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2020)
The purpose of this research is to find the effects of free cash flow, leverage, profitability, liquidity and firm size to dividend policy. This research using a sample of 21 LQ 45 companies registered in BEI 2015-2017. The method used is purposive sampling. Hypothesis testing in this research using multiple linear regression analysis. The result of this research show leverage, profitability, and firm size significantly affect the dividend policy. While free cash flow and liquidity have no effect on dividend policy